2009
DOI: 10.1123/jsr.18.1.24
|View full text |Cite
|
Sign up to set email alerts
|

The Hip’s Influence on Low Back Pain: A Distal Link to a Proximal Problem

Abstract: Low back pain (LBP) is a multifactorial dysfunction, with one of the potential contributing factors being the hip joint. Currently, research investigating the examination and conservative treatment of LBP has focused primarily on the lumbar spine. The objective of this clinical commentary is to discuss the potential link between hip impairments and LBP using current best evidence and the concept of regional interdependence as tools to guide decision making and offer ideas for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 51 publications
0
23
2
1
Order By: Relevance
“…19, 89, 249, 266, 318 It has been suggested that altered movements of the hip and spine may contribute to the development of low back pain, as it may alter the loads placed on the lumbar facets and posterior spinal ligaments. 1, 190 Several authors have described restricted hip mobility in patients with low back pain as an indicator of positive response to interventions targeting the hip.…”
Section: Clinical Guidelines: Interventionsmentioning
confidence: 99%
“…19, 89, 249, 266, 318 It has been suggested that altered movements of the hip and spine may contribute to the development of low back pain, as it may alter the loads placed on the lumbar facets and posterior spinal ligaments. 1, 190 Several authors have described restricted hip mobility in patients with low back pain as an indicator of positive response to interventions targeting the hip.…”
Section: Clinical Guidelines: Interventionsmentioning
confidence: 99%
“…19, 89, 249, 266, 318 It has been suggested that altered movements of the hip and spine may contribute to the development of low back pain, as it may alter the loads placed on the lumbar facets and posterior spinal ligaments. 1, 190 Several authors have described restricted hip mobility in patients with low back pain as an indicator of positive response to interventions targeting the hip.…”
Section: Clinical Guidelines: Interventionsmentioning
confidence: 99%
“…18 Due to the patient’s history of spondylolysis, lumbar spine examination was necessary. Subjective and objective complaints were similar to those of the previous spondylolysis injury.…”
Section: Discussionmentioning
confidence: 99%